Psychosocial care for hospitalized young survivors after the terror attack on Utøya Island: A qualitative study of the survivors' experiences. Issue 1 (January 2019) - Bugge, Ingrid; Jensen, Tine K.; Nilsen, Lisa Govasli; Ekeberg, Øivind; Dyb, Grete; Diseth, Trond H.
Abstract: Objective: The objective of the study was to explore hospitalized youths' experiences with psychosocial care in the hospital after the shooting on Utøya Island, Norway, in 2011. Methods: 17 hospitalized youths were interviewed face-to-face 30–31 months after the attack. The interviews were analysed using interpretative phenomenological analysis (IPA). The initial reading and coding of the interviews was carried out inductively. To explore the emphasis placed on everyday conversation and ordinary interaction detected during the initial reading, the text was re-read while bearing in mind concepts from the research field of sociology concerning the therapeutic potential in commonplace conversations and situations. Results: The youths highlighted the need for health care workers to embrace essential aspects of their past, present and future. Therefore, three overarching categories emerged related to 1) Remembering the past, 2) Dealing with the present and 3) Preparing for the future. For each temporal category, two related subcategories were identified: Past: Engaging in the trauma narrative; Understanding the trauma reminders ; Present: Bringing back normalcy; Being there ; Future: Supporting confidence; Instilling trust . Conclusions: For the youths in the current study, talking with the hospital staff about their traumatic experiences was mostly perceived as positive and linked to various helpful outcomes. In addition to engaging in the trauma narrative, the staff needed to comprehend and address how the traumatic experiences and the hospitalization resulted in the survivors' extended fear and changed appraisals about the world and themselves. Having the time to stay physically and mentally close to the youths and engage in everyday interaction was crucial in rebuilding their sense of safety and bringing back normalcy. The hospital staff played a significant role in strengthening the survivors' confidence in own capabilities and trust in others. The different professionals in the hospital contributed to various aspects of psychosocial care, and both trauma-focused interventions and commonplace conversations and actions were emphasized as important and meaningful approaches.